The Role of Self-efficacy in Enhancing Employee Performance: A Phenomenological Analysis of Malaysian Hotel Sector - Ray Octafian; Dyah Palupiningtyas; Aletta Dewi Maria; Krisnawati Setyaningrum Nugraheni; Farah Nabilah Binti Yaacob; Nabilah Binti Muhammad (Badan Penerbit STIEPARI Press, 2025)
The hospitality industry faces significant challenges in maintaining consistent service quality amidst increasingly intense global competition. Employee Self-efficacy, or confidence in one’s own abilities, is a crucial factor influencing service performance; however, an in-depth understanding of its mechanisms within a multicultural context remains limited. This study aims to explore the Self-efficacy experiences of employees in international hotels in Malaysia and examine how these experiences impact their service performance. The findings reveal that employee Self-efficacy manifests in three key dimensions: confidence in technical abilities, adaptability, and interpersonal skills. The development of Self-efficacy occurs through four stages: acclimatization to workplace culture, experiential learning, internalization of organizational values, and the cultivation of specific expertise. Key supporting factors include comprehensive training systems, social support, fair reward systems, career development opportunities, team cultural diversity, and autonomy in decision-making. Self-efficacy plays a central role in determining the quality of hotel employee performance through complex mechanisms influenced by the multicultural workplace context. These findings provide theoretical contributions to the development of Self-efficacy theory within multicultural organizations and practical implications for human resource management in the hospitality industry.